1992
DOI: 10.1073/pnas.89.18.8517
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond spontaneous-emission studies of reaction centers from photosynthetic bacteria.

Abstract: Spontaneous emission from reaction centers of photosynthetic bacteria has been recorded with a time resolution of 50 fs. Excitation was made directly into both the special-pair band (850 nm) and the Qx band of bacteriochlorophylls (608 am). Rhodobacter sphaeroides R26, Rhodobacter capsuleas wild type, and four mutants of Rb. capsulatus were studied. In all cases the fluorescence decay was not single exponential and was well fit as a sum of two exponential decay components. The short components are in excellent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
151
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(164 citation statements)
references
References 24 publications
13
151
0
Order By: Relevance
“…We note in passing that there has been much speculation during the past few years on the origin of heterogeneity in the kinetics of RCs measured with very good signal-to-noise ratios (Du et al, 1992;Peloquin et al, 1994;Hamm et al, 1993;Stanley & Boxer, 1995) (and likewise observed here for the cavity mutants; see Figure 3). It is possible that small variations in the Mg content of the monomeric BChl B L or residual Mg in the chromophore in the H L site could be responsible for this, rather than more exotic explanations based on theoretical conjecture (Marchi et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…We note in passing that there has been much speculation during the past few years on the origin of heterogeneity in the kinetics of RCs measured with very good signal-to-noise ratios (Du et al, 1992;Peloquin et al, 1994;Hamm et al, 1993;Stanley & Boxer, 1995) (and likewise observed here for the cavity mutants; see Figure 3). It is possible that small variations in the Mg content of the monomeric BChl B L or residual Mg in the chromophore in the H L site could be responsible for this, rather than more exotic explanations based on theoretical conjecture (Marchi et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies on femtosecond spontaneous-and stimulated-emission studies have shown that for all RCs studied (Rb. sphaeroides R-26, (Du et al 1992);…”
Section: Charge-separation Kineticsmentioning
confidence: 99%
“…An additional time component has been assigned in this spectral region, and also around 1020 nm (12), that was attributed to the formation of B L -as an intermediate in the electron transfer process (8,9). Furthermore, fluorescence emission from P* has been found to decay with multiple time constants that extend from a few to hundreds of picoseconds (7,(12)(13)(14)(15)(16)(17)(18)(19)(20).…”
mentioning
confidence: 99%